Holographic p-wave superfluid in the AdS soliton background with R F-2 corrections - Lv, Yanmei; Qiao, Xiongying; Wang, Mengjie; Pan, Qiyuan; Qian, Wei-Liang [UNESP]; Jing, Jiliang (Elsevier B.V., 2020)
We investigate the holographic p-wave superfluid in the background metric of the AdS soliton with RF2 corrections. Two models, namely, the Maxwell complex vector field model and Yang-Mills theory, are studied in the above context by employing the Sturm-Liouville approach as well as the shooting method. When turning on the spatial components of the gauge field, one observes that, in the probe limit, the inclusion of RF2 corrections hinders the superfluid phase transition. On the other hand, however, in the absence of the superfluid velocity, it is found that the RF2 corrections lead to distinct effects for the two models. Regardless of either the RF2 correction or the spatial component of the gauge field, the phase transition of the system is observed to be always of the second order. Moreover, a linear relationship between the charge density and chemical potential is largely established near the critical point in both holographic superfluid models. (C) 2020 The Authors. Published by Elsevier B.V.